Nazwy stopni pokrewieństwa i powinowactwa rodzinnego w gwarach zachodniej Wielkopolski - Żuraszek-Ryś, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
In this article, the names of the degree of kinship and affinity of the family in the western parts of Greater Poland were analyzed, paying attention to the changes that have occurred in the analyzed group of lexis in the studied area over more than 50 years, i.e. since the 1970s, when field research was carried out for the Atlas języka i kultury ludowej Wielkopolski (Atlas of Greater Poland’s Folk Language and Culture), until the present. The Atlas material was compared with the lexical data that the author collected in 2024 at selected Atlas locations or near them. The analysis covered 27 terms of family relations and showed that transformations are occurring among this group of lexis. Some names are still used (where they were used before or in other locations), some have disappeared, and new names have appeared as well.